Humankind and nature : an endangered system of interdependence in today's globalising world - Wong, Albert; Wardega, Artur K. (Cambridge Scholars Publishing, 2014)
As climate change continues to batter the coastlines of North America and elsewhere, and as extreme weather events provide abundant proof of its reality, religious leaders can no longer ignore the fact that the human has become a geologic force, a force that must be re-educated and re-formed in order to guarantee safe passage into a sustainable future. Hopefully, Jesuits and their lay partners can continue to provide leadership in regard to this issue, correctly identified by Fr Adolfo Nicolás, SJ, as a top priority. In this particular context, the role of religions and their valuable contribu.